Learning about Theories of Change for the Monitoring and Evaluation of Research Uptake - and Barnett, Chris; Gregorowski, Robbie (IDS, 2013)
This paper captures lessons from recent experiences on using ‘theories of change’ amongst organisations involved in the research–policy interface. The literature in this area highlights much of the complexity inherent in the policymaking process, as well as the challenges around finding meaningful ways to measure research uptake. As a tool, ‘theories of change’ offers much, but the paper argues that the very complexity and dynamism of the research-to-policy process means that any theory of change will be inadequate in this context. Therefore, rather than overcomplicating a static depiction of change at the start (to be evaluated at the end), incentives need to be in place to regularly collect evidence around the theory, test it periodically, and then reflect and reconsider its relevance and assumptions.